2012
DOI: 10.1111/j.1365-3016.2011.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal education inequalities in height growth rates in early childhood: 2004 Pelotas birth cohort study

Abstract: SummaryMatijasevich A, Howe LD, Tilling K, Santos IS, Barros AJD, Lawlor DA. Maternal education inequalities in height growth rates in early childhood: 2004 Pelotas birth cohort study. Paediatric and Perinatal Epidemiology 2012; 26: 236–249.Socio-economic inequalities in attained height have been reported in many countries. The aim of this study was to explore the age at which maternal education inequalities in child height emerge among children from a middle-income country. Using data from the 2004 Pelotas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
4
24
1
1
Order By: Relevance
“…Similar findings on the importance of maternal education, particularly in early life, have been described in a longitudinal study in Brazil. Matijasevich et al showed that maternal education was positively associated with differences in growth rates in height/length < 2.5 years of age (though not from 3 to 12 months) and that there was a lack of association later in childhood up to 4 years (Matijasevich et al, ). Busert et al () did not find an association with height for age difference in a mountainous region of Nepal; however, childhood stunting has been shown to be more common when mothers have no education than when they complete school or higher education in Nepal (Ministry of Health and Population [Nepal] et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings on the importance of maternal education, particularly in early life, have been described in a longitudinal study in Brazil. Matijasevich et al showed that maternal education was positively associated with differences in growth rates in height/length < 2.5 years of age (though not from 3 to 12 months) and that there was a lack of association later in childhood up to 4 years (Matijasevich et al, ). Busert et al () did not find an association with height for age difference in a mountainous region of Nepal; however, childhood stunting has been shown to be more common when mothers have no education than when they complete school or higher education in Nepal (Ministry of Health and Population [Nepal] et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Associations between stunting and birth weight (15, 44) or maternal height (3, 50) have also been identified in other studies. Disparities in linear infant growth can also be explained by maternal education (13, 43, 51). Finally, sex differences in stunting have been well described: 35.7% of boys and 28.3% of girls <5 y of age in Zimbabwe were stunted in 2010–2011 (52), which are typical of findings from several countries particularly in sub-Saharan Africa (53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was defined as a nominal variable of LAZ trajectory-group membership and covariates were maternal education, age, midupper arm circumference, and height and infant sex, birth weight, length, and gestational age on the basis of the documented associations of these variables with linear infant growth (5, 8, 10, 13, 15, 4045). To minimize the impact of collinearity on statistical inference, covariates were centered before model fitting.…”
Section: Methodsmentioning
confidence: 99%
“…Like Howe et al ,9 he suggested that height advantage may begin before school entry. In contrast, analyses of the Pelotas birth cohort from Brazil17 suggested widening inequalities in children’s length/height from birth to 4 years of age, with the magnitude of the deficit increasing from 0.2 of an SD unit at birth, to 0.7 of an SD unit at 4 years of age. Similarly, a Belarussian study found that children born to mothers with higher levels of education were longer at birth and grew faster than children of less educated mothers 18…”
Section: Introductionmentioning
confidence: 89%